Validation of the De Jong Gierveld Loneliness Scale in Peruvian old adults: a study based on SEM and IRT multidimensional models - Caycho-Rodríguez, Tomás (2023)
Loneliness is a public health problem. Its assessment is important to identify older adults who experience greater loneliness and appropriate interventions can be carried out. The De Jong Gierveld Solitude Scale (DJGLS) is one of the most widely used, at least in the European context, to measure loneliness. Although the Spanish version of the DJGLS has shown reliability and validity in Spanish samples of older adults, there is no evidence of adequacy in the Latin American context. Therefore, this study aims to evaluate the psychometric properties of the DJGLS in Peruvian older adults. Specifically, factorial validity, internal consistency and criterion-related validity were studied, based on a double analytical perspective: Classical Test Theory (SEM models) and Item Response Theory. The participants were 235 Peruvian older adults with ages ranging from 61 to 91 years old (Mean = 72.69, SD = 6.68) that assisted to Centers for the Elderly in the city of Trujillo, Peru. Together with the DJGLS, information from the three-item UCLA loneliness scale, Satisfaction with Life Scale, Brief Resilient Coping Scale and the Patient Health Questionnarie-2 was also gathered. The results support a one-dimensional structure of the DJGLS but with the presence of method effects associated to the negatively worded items. Additionally, the IRT multidimensional model applied also indicated the presence of a second dimension related to these negative items. Finally, other evidences of reliability and validity were adequate. In summary, the DJGLS may be considered a reliable and valid instrument to be used in the Peruvian (older adults) context.